Immigrant wages in the Spanish labour market: does the origin of human capital matter? - Esteban Sanromá; Raúl Ramos; Hipólito Simón (Institute for the Study of Labor (IZA), 2009)
The aim of this paper is to analyse the role played by the different components of human capital in the wage determination of recent immigrants within the Spanish labour market. Using microdata from the Encuesta Nacional de Inmigrantes 2007, the paper examines returns to human capital of immigrants, distinguishing between human capital accumulated in their home countries and in Spain. It also examines the impact on wages of the legal status. The evidence shows that returns to host country sources of human capital are higher than returns to foreign human capital, reflecting the limited international transferability of the latter. The only exception occurs in the case of immigrants from developed countries and immigrants who have studied in Spain. Whatever their home country, they obtain relatively high wage returns to education, including the part not acquired in the host country. Having legal status in Spain is associated with a substantial wage premium of around 15%. Lastly, the overall evidence confirms the presence of a strong heterogeneity in wage returns to different kinds of human capital and in the wage premium associated to the legal status as a function of the immigrants' area of origin.
urn:nbn:de:101:1-20090513555
Keywords: J15; J24; J31; J61; 330; Immigration; wages; human capital; Migranten; Lohnstruktur; Einwanderung; Bildungsertrag; Spanien